Syntax Course Impacts On Students' English Language Skill: Students' Perspective - Azra Batrisyia Sabrina; Khairunnisa Khairunnisa; Kezia Elizanti Purba; Lailatul Fitria; Siti Ismahani (Jurnal Pendidikan dan Sastra Inggris, 2024)
This study aims to find out and understand students' perspectives regarding the impact of syntax courses on their ability to speak English. This is motivated by the gap between theoretical understanding and practical application of syntax in the real world. To answer these problems, this study used a descriptive qualitative case approach to capture the comprehensive picture needed to answer the research questions. The data collection technique used interviews, by interviewing a number of students by asking 3 questions regarding the impact of syntax courses on their English language skills. The research was conducted at one of the Islamic Universities in Medan. The researcher interviewed 10 students who had studied the syntax course. The findings of the interviews are described descriptively. From the 3 questions asked, the results showed that: 1) During studying syntax in one semester, students can improve their knowledge of grammar and basic rules of English sentence structure: motivating them to better understand tree diagrams. 2) The impact of syntax course on students' language skills is the impact on writing, reading, and listening skills but the greatest impact on writing skills. Thus, syntax courses have a very positive impact on students' English language skills, not only in theoretical understanding but also in practical application.